Urban Livability Assessment in South Korea: Incorporating Climate Change Vulnerability - Sunmin Jun; Juchul Jung (Urban Science)
This study aims to develop an urban livability assessment index that incorporates climate change vulnerability and to apply this index to urban areas in South Korea, thereby analyzing the impact of climate change on living environments and quality of life. Existing frameworks for livability indices often fail to adequately reflect the long-term risks associated with climate change. Consequently, this research proposes a new livability index that includes climate change vulnerability, establishing a policy foundation aimed at protecting and enhancing the quality of life for urban residents. The methodology integrates existing livability indicators with climate change vulnerability indicators across 219 cities and districts in South Korea. Utilizing panel regression analysis and Local Indicators of Spatial Association (LISA) analysis, the study evaluates the spatial clustering characteristics and potential risks in each area. The results indicate that urban infrastructure significantly influences livability, with climate change vulnerability indicators forming high clusters primarily in southern regions. Furthermore, the study confirms economic disparities within the metropolitan area, as well as the exacerbation of social inequalities in regions vulnerable to disaster safety and social services. This research underscores the necessity of integrating climate change vulnerability into livability indices, suggesting that such indices can serve as critical criteria for urban policy formulation and the evaluation of regeneration projects.